2020
DOI: 10.1002/bab.2062
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone inhibits IL‐7‐induced tumor progression and metastatic invasion in prostate cancer cells by attenuating matrix metalloproteinase activity and Akt/NF‐κB signaling

Abstract: Interleukin (IL)‐7 acts via the IL‐7 receptor in metastatic tumor progression in prostate cancer (PC). The current study aimed to evaluate thymoquinone (Tq), an active constituent from Nigella sativa against IL‐7–driven tumor progression and metastatic invasion in PC cells. The 3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide (MTT) assay was used to assess the proliferation of PC cells. Enzyme‐linked immunosorbent assay was used to detect the expression of IL‐7 and matrix metalloproteinases (MMPs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…MMP-3 and MMP-7 drive the IL-7-induced tumor progression, migration, and invasion of DU-145 cells. Thymoquinone (Tq) treatment suppresses the activation of MMPs via IL-7/AKT/NF-κB signaling that inhibits IL-7-induced tumor progression and metastatic invasion in DU145 cells [82].…”
Section: Inflammatory Signaling and The Ecm Network Of The Tmementioning
confidence: 99%
“…MMP-3 and MMP-7 drive the IL-7-induced tumor progression, migration, and invasion of DU-145 cells. Thymoquinone (Tq) treatment suppresses the activation of MMPs via IL-7/AKT/NF-κB signaling that inhibits IL-7-induced tumor progression and metastatic invasion in DU145 cells [82].…”
Section: Inflammatory Signaling and The Ecm Network Of The Tmementioning
confidence: 99%
“…[14] The anticancer effect of TQ has been reported in different types of cancers including prostate cancer, osteosarcoma, fibrosarcoma, myeloblastic leukemia, colorectal carcinoma, and lung cancer. [15][16][17][18] In our present study, the antioxidant, antiproliferative, and apoptosis-inducing effects of TQ were analyzed to explore its anticancer efficacy against B(a)P-induced lung cancer in mice.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ] The anticancer effect of TQ has been reported in different types of cancers including prostate cancer, osteosarcoma, fibrosarcoma, myeloblastic leukemia, colorectal carcinoma, and lung cancer. [ 15–18 ]…”
Section: Introductionmentioning
confidence: 99%
“…13 TQ is one of the components extracted from Nigella sativa seeds and it has been reported to have antioxidant, 14 anti-inflammatory, 15 and anticancer effects. 16 Moreover, studies revealed that TQ could inhibit cancer cells growth and induce apoptosis in many malignancies such as breast, 17 lung, 18 colon, 19 pancreas, 20 prostate, 21 ovary cancers, 22 and leukemia. 23 However, along with its benefits, it showed inhibitory effects on CYP2C19, CYP2C9, CYP2D6, and CYP3A4, and it can cause herb-drug interactions.…”
Section: Introductionmentioning
confidence: 99%